AN OVERVIEW OF THE DYADIC, INTERGENERATIONAL AND DIGITAL-BASED REMINISCENCE THERAPY: A SCOPING REVIEW - Md Nasir, Nur Fatihah; Subramaniam, Ponnusamy; Ghazali, Shazli Ezzat; Sharma, Shobha; Md Hassan, Jasmah; Teh, Hoon Lang (Malaysian Journal of Public Health Medicine, 2023)
The reminiscence therapy approach is a non-pharmacological psychosocial intervention utilized for dementia management. Despite its potential benefits, there is a notable dearth of empirical studies within the Malaysian context. Consequently, a scoping review was conducted to evaluate the efficacy of this intervention in conjunction with caregivers and to elucidate its impact on the reminiscence process through communication. This review also considered the dyadic approach, involving a caregiver or volunteer in the intervention. Four reputable databases were systematically queried to identify relevant studies, resulting in the inclusion of thirteen articles after a stringent selection process. These studies exhibited diverse modes of communication. Upon comprehensive examination, it was discerned that intergenerational and digital forms of reminiscence therapy demonstrated efficacy akin to that of the traditional physical modality. This finding suggests the potential for broader implementation of these methods in future research endeavors, which may ultimately lead to improved communication and enhanced quality of life for individuals afflicted by dementia